Prevalence of Allergic Rhinitis in Patients Diagnosed with Chronic Rhinosinusitis in a Tertiary Care Hospital - Mumtaz Ahmad Umar, Mohibullah Mushwani, Ayesha Jawad, Mirza Nasheed Baig, Nighat Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic rhinosinusitis (CRS) is an inflammatory disorder of the nose and paranasal sinuses lasting for 12 weeks or longer. Aim: To explore the prevalence of allergic rhinitis and common allergens in chronic rhinosinusitis patients. Methods: The study was conducted in Department of ENT at Dr. Akbar Niazi Teaching Hospital Islamabad from April 2021 to March 2022. On the basis of inclusion criterion, one hundred patients of CRS included in this study. All patients met the diagnostic criteria for CRS through, history, nasoendoscopic examination, and radiological findings. Allergic rhinitis was diagnosed on the basis of skin prick test (SPT). All patients who were operated for CRS were excluded from the study. Results: Male and female ratio was almost equal with slight male predominance. The incidence of polypoidal CRS and non-polypoidal CRS was 52 (52%) and 48 (48%) respectively. Almost two third of polypoidal CRS patients suffered from severe disease based on Nasoendoscopic examination and radiological findings (CT-Scan). The commonest presenting symptoms were nasal discharge and nasal blockage effecting around 92% and 91% patients respectively. Skin prick test (SPT) showed 73% patients were suffering from allergic rhinitis with pet dander being the most common allergen. Conclusion: Chronic Rhinosinusitis is a common disease and majority of patients develop CRS secondary to allergic reaction. Early diagnosis of allergic rhinitis with identification of specific allergens and its management can help in prevention of CRS.